Development of a 3D model to predict curing dimensions and conversion rates of curable ceramic systems during stereolithography 3D printing process. Issue 13 (October 2022) - Vallet, D.; Pateloup, V.; Michaud, P.; Chartier, T.
Abstract: To meet industry's expectations for manufacturing ceramic parts by stereolithography, a better comprehension of the process, in particular laser scattering through the ceramic slurry is mandatory. This knowledge makes it possible to define adapted printing conditions to control the dimensions, homogeneity of the conversion and mechanical properties of the green parts, in order to achieve better resolutions and optimize the properties of sintered parts. This approach is focused on the development of a 3D polymerization modeling for stereolithography process able to predict curing and associated thermal phenomena. First, a design of experiments is carried out to identify material-dependent parameters, calibrate and validate the model, then able to predict monomer conversion rates and dimensions after curing depending on manufacturing parameters. Finally, temperature variation and exposure homogeneity have been evaluated. These results will allow, in future studies, to interpret the differences of deformations and mechanical properties of green parts.